Antibacterial Activity of Ethanol Extract from Stem Bark and Leaves of Berenuk (Crescentia cujete L.) - Uswatun Hasanah; Desi Rosdiana; Syaefudin Syaefudin (Current Biochemistry, 2017)
Crescentia cujete L. (C. cujete) has been known as a medicine for various diseases that caused by microorganisms. This research was aimed to identify the phytochemical compounds and to determine the antibacterial activity of ethanolic extracts from stem bark and leaves of C. cujete. The phytochemical compounds in both extracts were identified by Harborne method, while antibacterial activity assay was performed by disc diffusion method with the concentration of bacteria 106 cfu/mL. Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were used in antibacterial assay. Minimum Inhibitory Concentration (MIC) was obtained by using contact method. The phytochemical compounds analysis showed that ethanol extracts of C. cujete stem bark and leaves contained alkaloids, flavonoids, saponins, tannins, and steroids. The results of antibacterial activity test showed that both extracts have antibacterial activity with the highest inhibition showed by extracts with concentration of 100 %(w/v). The decreased percentage in the number of bacterial colonies on the extracts was less than 90 % so that the MIC value of both extracts against S. aureus could not be determined.